Analysis of Working Time Standard for Loading and Unloading Goods And Income for Loading Unloading Labor (Tkbm) at Traditional Shipping Quay of Sunda Kelapa Port - Edward Marpaung; Paulus Raga; Yolla Ayutia; Langas Denny Siahaan; Febriani Paembong (Jurnal Ilmu Multidisiplin, 2025)
Sunda Kelapa Port is one of the largest ports in Indonesia that specifically handles traditional ships activities. The loading and unloading services of various commodities at this port are still not optimal in accordance with the complaints of service users. In this regard, this study is aimed at finding various root causes of suboptimal loading and unloading activities through measuring the standard time of loading and unloading activities and analyzing the income level of stevedoring workers (TKBM). This type of research is quantitative research to measure standard time against six commodities as a sample with time and motion study analysis methods. The results of the analysis showed that the standard time obtained in the six commodities sampled was unloading oilcake, sago and kaolin by 7 minutes, 8 minutes, 9 minutes and for loading salt, rice and fertilizer by 7.4 minutes, 7.3 minutes and 7.3 minutes with income levels for unloading work of 200%, 200% and 238% of payroll calculations with real time and for loading work of 205%, 200% and 200% of payroll calculations with real time. The productivity of unloading work is 20.88% and loading is 14.87%, meaning that loading and unloading work at Sunda Kelapa Port has not met the loading and unloading performance standards of non-container goods in accordance with the Regulation of the Director General of Sea Transportation.